2019
DOI: 10.1039/c9ta00085b
|View full text |Cite|
|
Sign up to set email alerts
|

A facile method for synthesizing CuS decorated Ti3C2 MXene with enhanced performance for asymmetric supercapacitors

Abstract: A Ti3C2–CuS//Ti3C2 asymmetric supercapacitor device exhibited an energy density of 15.4 W h kg−1 at a power density of 750.2 W kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(155 citation statements)
references
References 52 publications
9
138
2
Order By: Relevance
“…Aside from the thermal annealing, the (hydro‐)solvothermal method is also effective for the formation of MXene‐inorganic nanostructure composites with high crystallinity. Pan et al reported a sandwich‐like Ti 3 C 2 /CuS composite through the reaction of Cu(NO 3 ) 2 ·3H 2 O, thioacetamide (TAA) and Ti 3 C 2 powders in the ethylene glycol solution at 150 °C for 9 h . Due to the electrostatic interaction, the positively charged Cu 2+ ions are uniformly attracted onto the surface of negatively charged Ti 3 C 2 , forming a homogeneous composite upon the solvothermal treatment.…”
Section: Mxene Compositesmentioning
confidence: 99%
“…Aside from the thermal annealing, the (hydro‐)solvothermal method is also effective for the formation of MXene‐inorganic nanostructure composites with high crystallinity. Pan et al reported a sandwich‐like Ti 3 C 2 /CuS composite through the reaction of Cu(NO 3 ) 2 ·3H 2 O, thioacetamide (TAA) and Ti 3 C 2 powders in the ethylene glycol solution at 150 °C for 9 h . Due to the electrostatic interaction, the positively charged Cu 2+ ions are uniformly attracted onto the surface of negatively charged Ti 3 C 2 , forming a homogeneous composite upon the solvothermal treatment.…”
Section: Mxene Compositesmentioning
confidence: 99%
“…[ 23 ] The excellent electrochemical properties of MXenes make them widely applicable for electromagnetic interference shielding, [ 24–25 ] photodegradation, [ 26 ] photovoltaics, [ 27–28 ] electrochemical catalysis, [ 29 ] supercapacitors, and lithium ion batteries. [ 30–32 ] MXenes are prepared from MAX phases by etching the A layer (usually Al or Si) with a strong acid solution such as HF or LiF/HCl. [ 33 ] The general formula of MXenes is M n +1 X n T x ( n = 1–3), where M represents an early transition metal such as Ti, V, Nb, Ta, or Mo, X is C and/or N, and T x represents a surface terminating group such as O, F, and OH.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure d) Those results are higher than some of the carbon‐based anode materials (Table S1), such as carbon nanofibers (104.5 F g −1 ), N,S‐doped carbon‐silica nanospheres (221 F g −1 ) and nitrogen‐doped pomelo mesocarps‐based carbon (223 F g −1 ), etc. In addition, the obtained capacity and rate capability are even comparable or higher than some of the pseudocapacitive anode materials such as Ti 3 C 2 Mxene (169.5 C g −1 , 60 %), hierarchical hollow Ni/VN microsphere (143.2 F g −1 , 70.5 %) and MoO 2 ‐C nanofilm (208.4 F g −1 , 47 %), etc.…”
Section: Resultsmentioning
confidence: 84%